STRATESTRATEGI PEMBELAJARAN IPS PADA ANAK SEKOLAH DASARGI PEMBELAJARAN IPS PADA ANAK SEKOLAH DASAR - Aliyah; Rafika Silfiyanty; Rifa'i; Sastra Wijaya (STKIP Subang, 2026)
A good and appropriate learning process affects the quality of learning. In order to improve the quality of education, the hope is that learners understand what they learn and can be applied in real life. Therefore, teachers are required to have innovative knowledge so that in the learning process not only the teacher is active but also the students. Strategy is a very important tool in achieving learning objectives. Active learning strategies are designed to create a learning atmosphere that stimulates active student involvement in the learning process, so that students have an attitude of independence, are able to think critically, and creatively. Therefore, educators are required to be creative in carrying out various strategies that are in accordance with the material and are expected to be easily accepted by students. Innovative learning will make students interested in learning and trigger the emergence of creativity in students. Social studies learning strategies should be designed as much as possible to achieve a learning process that is easy to understand. Social studies is a social subject that covers various aspects such as social life, and includes structures that exist on earth. The approach used in this research is a literature study. Where researchers analyze a number of journals and articles from relevant previous research.